Impacto da cárie dentária na qualidade de vida de crianças pré-escolares: um estudo de coorte prospectivo - Raquel Goncalves Vieira de Andrade (2015)
Early childhood caries (ECC) is one of the most common adverse oral health conditions among preschool children and is considered a public health problem associated with an impact on quality of life. The aim of the present study was to evaluate the influence of socioeconomic factors, oral problems and the oral health-related quality of life (OHRQoL) on the incidence of untreated dental caries among preschool children. A prospective cohort study was conducted with a sample of 288 preschool children in the city of Diamantina, state of Minas Gerais, Brazil. The first exam (T1) was performed during national vaccination campaigns in 2010 and 2011 and involved children aged 24 to 47 months, who were reevaluated two years afterward (T2) at preschools in the city. The children were allocated to two groups based on baseline (T1) information: caries free (n = 144) and exposed to untreated caries (144). Untreated caries was evaluated using the dmft index at T1 and T2 through a clinical exam performed by a dentist who had undergone a training exercise (Kappa = 0,91). Parents/caregivers filled out a form addressing socioeconomic data and answered the Brazilian version of the Early Childhood Oral Health Impact Scale (B-ECOHIS) to access the oral heath related quality of life both T1 and T2. The presence/absence of new untreated caries at T2 was the dependent variable. Data analysis involved descriptive statistics, the Mann-Whitney test, univariate Poisson regression and a hierarchical multivariate model (p<0.05; 95% CI). The incidence of untreated dental caries was 41.3% (n=119). Considering the severity of untreated dental caries, the incidence of new carious lesions was 28.4% among the children who were caries free at T1, 48.4% among those with low caries severity at T1 and 65.9% for those with high caries severity at T1. Both low (RR=1.63; 95% IC: 1.18-2.26; p<0.001) and high (RR=1.92; 95% IC: 1.36-2.72; p<0.001) severity untreated caries, household income less than two times the Brazilian monthly minimum wage (RR=1.79; 95% IC: 1.04-3.25; p=0.042) and total B-ECOHIS score (RR=1.03; 95% IC: 1.02-1.05; p<0.001) at T1 were risk factors for the incidence of untreated dental caries among the preschool children at T2. In conclusion, the severity of untreated dental caries, monthly household income and total B-ECOHIS score were risk factors for the incidence of untreated dental caries among the preschool children analyzed.